Comparison of immediate-load mini dental implants and conventional-size dental implants to retain mandibular Kennedy class I removable partial dentures: A randomized clinical trial - Waruth Threeburuth (2018)
© 2018 Wiley Periodicals, Inc. Background: Complications of distal extension mandibular removable partial dentures are: loss of retention, irritation, and so forth. Dental implants have been used to support distal extension removable partial dentures. However, many patients have limited bone support in which to place conventional-size dental implants. Purpose: To compare the clinical outcomes of using immediate-loaded mini dental implants and immediate-loaded conventional-size dental implants, when used to retain mandibular Kennedy class I removable partial dentures. Materials and Methods: Thirty patients were randomly divided into two groups. Mini dental implants and conventional-size dental implants were placed in participants in the first molar region on both sides. The dentures were connected immediately. Patients were recalled on 1, 3, 6, and 12months after surgery. Digital periapical radiographs were made, and patient satisfaction was recorded. Data were analyzed by independent samples t-test and paired samples t-test (P=.05). Results: Twenty eight of the implants survived (survival rate=93.3%) in each group. Mean radiographic bone loss was 0.47±0.42 and 1.03±1.07mm in groups 1 and 2, respectively. Conventional-size implants revealed significantly greater marginal bone loss than mini implants (P=.01). Patient satisfaction showed significant improvement after treatment in both groups. Conclusions: Immediate-loaded mini dental implants can be applied for retaining mandibular Kennedy class I removable partial dentures with very favorable results.